IDENTIFIKASI BAKTERI POTENSIAL PROBIOTIK PADA SALURAN PENCERNAAN IKAN BAWAL AIR TAWAR (Colossoma macropomum) Identification of Potensial Bacteria of Probiotics in The Digestive Tract of Fresh Water Bream (Colossoma macropomum) - Erna Lestari Indah Nababan; Dwi Suryanto; Indra Lesmana (AQUACOASTMARINE, 2018)
Probiotic are considered as beneficial bacteria. They may live in digestive tract of vertebrate including fish. Probiotic bacteria can inhibit the growth of pathogenic bacteria and improve water quality as well as control of bacterial diseases that occur in fish culture. They may suppress bacterial population through competition by producing antimicrobial compounds or through nutritional competition in the intestinal wall. Bawal (Colossoma macropomum) is a fish commodity that have high economic value and one of the ornamental fish that can be consumed. This study aimed to determine the potential probiotic bacteria live in the digestive tract of Bawal. The study was conducted to isolate and to identify potential bacterial species of probiotics that had been isolated.The results showed that potential probiotic bacteria in the digestive tract of Bawal were Enterococcus faecalis, Stapylococcus saprophyticus, Micrococcus luteus and Bacillus cereus.Keywords : Probiotic Bacteria, Enterococcus faecalis, Stapylococcus saprophyticus, Micrococcusluteus, Bacillus cereus.